2020
DOI: 10.1111/1462-2920.15349
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic insights into the metabolism and evolution of a new Thermoplasmata order (Candidatus Gimiplasmatales)

Abstract: Thermoplasmata is a widely distributed and ecologically important archaeal class in the phylum Euryarchaeota. Because few cultures and genomes are available, uncharacterized Thermoplasmata metabolisms remain unexplored. In this study, we obtained four medium-to high-quality archaeal metagenome-assembled genomes (MAGs) from the filamentous fragments of blackodorous aquatic sediments (Foshan, Guangdong, China). Based on their 16S rRNA gene and ribosomal protein phylogenies, the four MAGs belong to the previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 84 publications
1
27
0
Order By: Relevance
“…The diversity of Nitrososphaerales was also reported from natural ecosystems and agricultural soil, where it was overrepresented in wet land and soil from tea plantations (Lynn et al, 2017). Thermoplasmata have a mixotrophic lifestyle that involves CO2 fixation as well as formaldehyde and acetate assimilation, and they have important potential functions in the carbon, sulfur, and arsenic processes (Hu et al, 2020). Thermoplasmata in our study showed decreased trends under consecutive monocropping, the abundance was higher in both T1and T2, which then decreased in T3 (Figure 4c).…”
Section: Discussionmentioning
confidence: 83%
“…The diversity of Nitrososphaerales was also reported from natural ecosystems and agricultural soil, where it was overrepresented in wet land and soil from tea plantations (Lynn et al, 2017). Thermoplasmata have a mixotrophic lifestyle that involves CO2 fixation as well as formaldehyde and acetate assimilation, and they have important potential functions in the carbon, sulfur, and arsenic processes (Hu et al, 2020). Thermoplasmata in our study showed decreased trends under consecutive monocropping, the abundance was higher in both T1and T2, which then decreased in T3 (Figure 4c).…”
Section: Discussionmentioning
confidence: 83%
“…The selected topology largely agrees with the 16S rRNA gene phylogenetic tree (Figure S5). The Lutiacidiplasmatales order forms a monophyletic clade with the methanogenic Methanomassiliicoccales 34 and the recently described order-level groups Gimiplasmatales 13 , SG8-5 35 and Lunaplasmatales 10 (Figure 2).…”
Section: Resultsmentioning
confidence: 91%
“…Several contrasting evolutionary histories have been previously proposed for the Thermoplasmatota 5, 10, 13, 33 , particularly with the divergent placement of the clades Poseidoniales and Thermoprofundales. Therefore, our study provides an updated and robust phylogeny of the Thermoplasmatota (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within these genomes, Hu et al identify consistent groups of genes that could be capable of metabolizing complex organic compounds as well as de-novo synthesis of nucleic acids and mevalonate. Zhong et al (2021) report the expansion of accessory genes in the genomes of Thermococcales, and Hu et al (2021) provide evidence that one mechanism for such expansion is lateral gene transfer. The genomes of Candidatus Gimiplasmatales include genes for arsenic detoxification and cell motility.…”
Section: 'Ecophysiology Of Extremophiles' Special Issuementioning
confidence: 99%